Juvenile polyps of the colon and rectum - Alhan, Etem; Ünüvar, Erhan; Gümüştekin, Enis (The Turkish Journal of Pediatrics, 1988)
Fifty-two patients with juvenile polyps of the colon examined over a four-year period are presented. There were thirty males and twenty-two females. The most common symptoms were bleeding and anemia. 96.7% of the polyps were located in the rectum. Forty-four patients had a solitary polyp and the remainder, multiple polyps. The single polyps in the rectum were ligated and excised in direct vision under general anesthesia. The diagnosis of familial juvenile polyposis coli was confirmed by one biopsy. The patients were given periodic examinations of the colon with a sigmoidoscope and the administration of barium enemas.